TRAINING KIT ELECTRIC MIRROR - , BAYU MARANTA PRASETYADI, Ir. Andr. Surjaka, Isp, MT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Electrical mirror is system on the vehicle that is used to drive the outside rearview mirror is electric motor using DC and switch. This system was used on the car today, because to make it easy for the driver in the rear-view mirror set without having struggled so that the driver can conserve energy. Therefore we make a tool kit training electric mirror system. With this tool we can figure out how to work the system electrically mirror or as a method of learning In the manufacturing process will be discussed the making of the design order training kit, panel board design, planning tools and materials to be used and planning work. Creation of training kit electric mirror system is divided into three process, namely the application of the design acrylic panel on the board, frame manufacture, and installation of components. With the creation of training this kit so the praktikan can divide groups in small amounts so they can better understand the said system electric mirror on a car's rear view mirror.